2003
DOI: 10.1074/jbc.m301009200
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Prostaglandin F2α, Bimatoprost (Prostamide), and Butaprost (EP2 Agonist) on Cyr61 and Connective Tissue Growth Factor Gene Expression

Abstract: Connective tissue growth factor (CTGF) and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 33 publications
1
54
0
2
Order By: Relevance
“…EP 2 -mediated CCN1/Cyr61 expression is via Rho and MAP kinase pathways. Butaprost triggers G s protein-coupled receptor activation mechanism, which involves activation of adenylate cyclase and initiation of the cAMP pathway with resultant activation of protein kinase A [Liang et al, 2003].…”
Section: Pathways Involved In Ccn1/cyr61 Inductionmentioning
confidence: 99%
“…EP 2 -mediated CCN1/Cyr61 expression is via Rho and MAP kinase pathways. Butaprost triggers G s protein-coupled receptor activation mechanism, which involves activation of adenylate cyclase and initiation of the cAMP pathway with resultant activation of protein kinase A [Liang et al, 2003].…”
Section: Pathways Involved In Ccn1/cyr61 Inductionmentioning
confidence: 99%
“…It was reported that Cyr61 mRNA (factor involved in tissue remodeling) expression was upregulated through EP 2 receptor stimulation in the isolated cat iris [69] and human ciliary smooth muscle cells and that a non-selective EP receptors agonist induced proMMP-1 and -3 secretion in ciliary muscle cells [70]. Currently unknown is whether EP 2 specifically mediates the secretion of MMPs and ECM turnover in TM cells.…”
Section: Prostaglandin Ementioning
confidence: 99%
“…Bimatoprost activates signaling pathways in different cells from PGF 2α in the same cat iris sphincter preparation by mechanisms unrelated to conversion to prostaglandins, activation of prostanoid receptors, enhancement of anandamide levels or gating of TRPV1 vanilloid receptors [87,88]. Bimatoprost also potently contracts tissues, such as uterus [89] and stimulates Cyr 61 expression in ciliary muscle cells, with mechanisms that are distinct from that of PGF 2α [69]. Additionally, prostamide F 2α and its analogue bimatoprost exhibit activities at recombinant FP and native FP receptors, including those in TM cells, with a concentration 1000 times higher than PGF 2α and its derivatives.…”
Section: Prostamidesmentioning
confidence: 99%
“…Es wird angenommen, dass die Wirkung auf den trabekulären und den uveoskleralen Abflussweg nicht alleine über Prostaglandin-Rezeptoren erfolgt, sondern auch über eigene Prostamid-Rezeptoren [9]. Neben den häufig beschriebenen Nebenwirkungen wie Hyperpigmentierung der periokulären Haut und der Iris, gesteigertem Zilienwachstum, konjunktivaler Hyperämie und zystoidem Makulaçdem gibt es auch Berichte über HSV-Keratitis-Reaktivierungen und Iritiden [7,8,14].…”
unclassified